Catamenial pneumothorax after multiple failed in vitro fertilization cycles - Milačić, Bojan; Vujadinović, Obrad; Vukčević, Batrić; Milić, Petar (Vojnosanitetski pregled, 2021)
Introduction. Catamenial pneumothorax is spontaneous pneumothorax occurring within 72–96 h before and after menstrual bleeding. It is frequently associated with thoracic endometriosis. However, certain cases are not associated with any identifiable thoracic pathology. Case report. A 42-year-old woman with a history of pelvic endometriosis presented with sudden cough and shortness of breath on the first day of menstrual bleeding. Chest radiography revealed a complete right pneumothorax. The patient had previously undergone 7 failed in vitro fertilization cycles. Video-assisted thoracoscopic surgery showed pulmonary bullous lesions and a diaphragmatic fenestration. Atypical resection of the pulmonary apex was performed by an endostapler. Diaphragm plication was performed using Ethibond sutures. Definitive histopathological examination of the pulmonary tissue was negative for endometriosis. A postoperative course of gonadotropin-releasing hormone (GnRH) agonist triptorelin was administered during a period of 6 months. The patient’s postoperative recovery was uneventful, without recurrence of pneumothorax to this day. Conclusion. There is a possibility that ovarian hyperstimulation caused the rupture of the pulmonary bullae. The patient may have developed endometriotic diaphragmatic fenestrations, activated by ovarian hyperstimulation, leading to pneumothorax. Early diagnosis and timely surgical treatment dealing with all thoracic pathology, as well as adjuvant hormonal treatment, may reduce the recurrence rate of catamenial pneumothorax.